Real Time Harmonic Analysis of Recuperative Current through Utilization of Digital Measuring Equipment - Spanik, P.; Sedo, J.; Drgona, P.; Frivaldsky, M. (Elektronika ir Elektrotechnika, 2013)
This paper deals with device for online, real time analysis of recuperative current with use of microprocessor. This system is used in railway transport for measurement and analysis of recuperative-currents from converter in railway engine. Recuperative currents from converters in railway engines, flows through rail back to the distribution point. Content of higher harmonics in these currents must not exceed limits specified in international standard UIC 550-3, so exact measurement and analysis of this harmonics is necessary. Proposed device uses microprocessor for real time measurement and analysis of recuperative currents. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.4364